Role of crotoxin, a phospholipase A2 isolated from Crotalus durissus terrificus snake venom, on inflammatory and immune reactions - Diva F. Cardoso; Monica Lopes-Ferreira; Eliana L. Faquim-Mauro; Mahasti S. Macedo; Sandra H. P. Farsky (Mediators of Inflammation)
Background: Crotoxin (CTX) is a potent neurotoxin from Crotalus durissus terrificus snake venom (CdtV) composed of two subunits: one without catalytic activity (crotapotin), and a basic phospolipase A2. Recent data have demonstrated that CdtV or CTX inhibit some immune and inflammatory reactions.